Malaria drives T cells to exhaustion - Wykes, Michelle N.; Horne-Debets, Joshua M.; Leow, Chiuan-Yee; Karunarathne, Deshapriya S. (Frontiers in Microbiology, 2014)
Malaria is a significant global burden but after >30 years of effort there is no vaccine on the market. While the complex life cycle of the parasite presents several challenges, many years of research have also identified several mechanisms of immune evasion by Plasmodium spp.. Recent research on malaria, has investigated the Programmed cell death-1 (PD-1) pathway which mediates exhaustion of T cells, characterized by poor effector functions and recall responses and in some cases loss of the cells by apoptosis. Such studies have shown exhaustion of CD4+ T cells and an unappreciated role for CD8+ T cells in promoting sterile immunity against blood stage malaria. This is because PD-1 mediates up to a 95% reduction in numbers and functional capacity of parasite-specific CD8+ T cells, thus masking their role in protection. The role of T cell exhaustion during malaria provides an explanation for the absence of sterile immunity following the clearance of acute disease which will be relevant to future malaria-vaccine design and suggests the need for novel therapeutic solutions. This review will thus examine the role of PD-1-mediated T cell exhaustion in preventing lasting immunity against malaria.